JUSTICE AND COMPENSATION FOR LAND ACQUISITION FOR COMMUNITIES AFFECTED BY INFRASTRUCTURE DEVELOPMENT - Gloria Gita Putri Ginting; Henry Aspan; Ari Prabowo; Etty Sri Wahyuni (RADJA PUBLIKA, 2026)
This study aims to analyze the fairness of land acquisition compensation for communities affected by infrastructure development in Indonesia. The main focus of the study is to examine the gap between normative provisions mandating